2018
DOI: 10.48550/arxiv.1807.02264
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Variance Reduction for Reinforcement Learning in Input-Driven Environments

Hongzi Mao,
Shaileshh Bojja Venkatakrishnan,
Malte Schwarzkopf
et al.

Abstract: We consider reinforcement learning in input-driven environments, where an exogenous, stochastic input process affects the dynamics of the system. Input processes arise in many applications, including queuing systems, robotics control with disturbances, and object tracking. Since the state dynamics and rewards depend on the input process, the state alone provides limited information for the expected future returns. Therefore, policy gradient methods with standard state-dependent baselines suffer high variance d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 19 publications
0
13
0
Order By: Relevance
“…The studies on applying reinforcement learning to non-Markovian environments is a longstanding research area [55], however, its applications in systems research and in particular resource management are not fully discovered. To the authors' knowledge the Mao et al [56] paper is the only research that has tackled one of the challenges of a semi-Markovian environment MDP in the area.…”
Section: Challenges Of Using Machine Learning For Resource Managementmentioning
confidence: 99%
“…The studies on applying reinforcement learning to non-Markovian environments is a longstanding research area [55], however, its applications in systems research and in particular resource management are not fully discovered. To the authors' knowledge the Mao et al [56] paper is the only research that has tackled one of the challenges of a semi-Markovian environment MDP in the area.…”
Section: Challenges Of Using Machine Learning For Resource Managementmentioning
confidence: 99%
“…The studies on applying reinforcement learning to non-Markovian environments is a longstanding research area [55], however, its applications in systems research and in particular resource management are not fully discovered. To the authors' knowledge the Mao et al [56] paper is the only research that has tackled one of the challenges of a semi-Markovian environment MDP in the area.…”
Section: Challenges Of Using Machine Learning For Resource Managementmentioning
confidence: 99%
“…Meanwhile, subtracting a baseline remains a heuristic [26] that has strong empirical but limited theoretical support. One possible benefit of a baseline is that it provides variance reduction [10], which has motivated work on designing alternative baselines that further reduce variance [30,4,20,31]. However, other work [7] has shown that variance reduction is not necessarily aligned with policy learning quality.…”
Section: Introductionmentioning
confidence: 99%